Reporting gaps in immunization costing studies: Recommendations for improving the practice. (7th August 2020) - Vaughan, Kelsey; Ozaltin, Annette; Moi, Flavia; Kou Griffiths, Ulla; Mallow, Michaela; Brenzel, Logan
Highlights: Poor practices and reporting oversights limit the understanding and use of immunization cost data. Our review identified reporting problems on the vaccines costed, types of costs, and data analysis. Our checklist offers a standard of practice for reporting on immunization costing studies. Reporting that adheres to this checklist will increase the interpretability and use of evidence. Abstract: High-quality evidence on the cost of delivering vaccines is essential for policymakers, planners, and donors to ensure sufficient, equitable, predictable, and sustainable financing. However, poor practices and reporting oversights in both the published and grey literature limit the understanding and usability of cost data. This paper describes quality assessment results and quantifies problems with immunization costing study reporting practices found in 68 articles and reports included in an immunization delivery unit cost repository focused on low- and middle-income countries and launched in 2018, the Immunization Delivery Cost Catalogue (IDCC). We recommend a standard of practice for writing up an immunization costing study, in the form of an easy to follow checklist, to increase the quality of reporting and the comparability of results. Reporting that adheres to this checklist will improve the comprehension and interpretability of evidence, increasing the likelihood that costing studies are understood and can be used for resource mobilization and allocation, planning and budgeting, and policy decisions.